2016
DOI: 10.1080/19443994.2015.1020514
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and adsorption study of Pb (II) toward different treated activated carbons derived from olive cake wastes

Abstract: A B S T R A C TAdsorption capacity of activated carbons (ACs) derived from olive cake toward Pb (II) was tested in batch single ion experimental mode as a function of time, pH, carbon dose, and initial ion concentration. Physicochemical properties were carried out for produced ACs and a commercial Organosorb 10-CO to elucidate the variations of observed results. The total pore volume reached 0.676 cm 3 g −1 for AC2 (activated under forced air); however, AC1 (activated under nitrogen) and Organosorb 10-CO had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Moreover, the original cellular morphology of the precursor was lost because a large part of the cellulosic structure has been degraded and extracted from the interior to the exterior of the particle (Marsh and Rodriguez-Reinoso, 2006b;El-Kady et al, 2015). Previous report suggested that the carbon surface chemistry is influenced by the presence of heteroatoms and has a great influence on both electrostatic and non-electrostatic interactions (El-Sayed and Bandosz, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the original cellular morphology of the precursor was lost because a large part of the cellulosic structure has been degraded and extracted from the interior to the exterior of the particle (Marsh and Rodriguez-Reinoso, 2006b;El-Kady et al, 2015). Previous report suggested that the carbon surface chemistry is influenced by the presence of heteroatoms and has a great influence on both electrostatic and non-electrostatic interactions (El-Sayed and Bandosz, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…The adsorption attained equilibrium in the third stage when the amount of metal ions adsorbed onto the NCH equaled the amount of metal ions desorbing from the NCH. The rapid adsorption at the initial stage is due to the availability of huge number of adsorptive sites (El-Kady et al, 2016;Egbosiuba et al, 2020) and a high external diffusion rate of metal ions (Doulia et al, 2009). Adsorption transfer from extra diffusion to internal diffusion was blamed for the subsequent delayed adsorption in the second stage, while the saturated adsorption stage is due to the electrostatic repulsion between metal ions and the adsorbent, which limits the function of the remaining activated sites (Doulia et al, 2009;Shi et al, 2009).…”
Section: Effect On Contact Timementioning
confidence: 99%
“…From this point of view, we are looking to use nano carbon material to sequester heavy metals from aqueous solution. The adsorption of trace metals in single metal solutions has been extensively studied (Girgis et al, 2009;Ibrahim et al, 2013;El-Kady et al, 2016); however, few publications have been devoted to the studies of simultaneous adsorption of metal ions from aqueous solutions (Bohli et al, 2017;Fang et al, 2018;He et al, 2018;Prelot et al, 2018;Liu et al, 2020). Therefore, the aim of current study is to investigate the ability of nanocarbon hybrid (NCH) to eliminate As, Fe, and Mn from aqueous solution under various conditions (contact time, pH, dose, initial metal concentration).…”
Section: Introductionmentioning
confidence: 99%
“…El‐Kady et al. 109 investigated the impact of the activating agent (H 3 PO 4 ) concentration on the synthesis of olive oil cake‐based activated carbon. They explored two ratios of olive oil cake to H 3 PO 4 , namely, 1:1.75 and 1:3, and found that a higher H 3 PO 4 concentration also increases the specific surface area from 793 to 835 cm 2 g −1 while decreasing the carbon content from 74.79 ± 1.54 % to 71.58 ± 1.32.…”
Section: Oil Cake‐based Biocarbon Materialsmentioning
confidence: 99%